Analisis Financial Distress pada Perusahaan Industri Department Store yang Terdaftar di Bursa Efek Indonesia Sebelum, Selama, dan Setelah Pandemi Covid-19 - Cahyadi, Arief; Mazelfi, Ihsani (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to determine the financial condition of department store companies and assess whether there are department store companies that have the potential to experience financial distress. This research is a type of descriptive quantitative research. The research sample was carried out by purposive sampling technique with the final number of samples, namely 3 department store industry companies listed on the Indonesia Stock Exchange (IDX) before, during, and after the Covid-19 pandemic with companies coded E73 based on the IDX Industrial Classification (IDX-IC. The research data used is secondary data sourced from the company's annual financial statements collected through access to the IDX's official website (www.idx.co.id) and the company's official website. The research data processing was carried out by applying data analysis techniques using the Altman Z-Score Modified analysis method. The novelty of this research is found in the department store industry and there are 3 research time periods. Conclusion based on the results of this research show that the financial condition of companies is different, namely financial distress, healthy (safe), and gray (gray). There is 1 company that has the potential to experience financial distress in 2020, namely PT Matahari Department Store, and 1 company that is included in the gray zone, namely PT Matahari Department Store in 2023. Based on the findings from the research, the implication is that companies whose financial condition has declined to be able to consider actions, especially from the results of the analysis of the values that form the Z Altman Z-Score to maintain their financial stability. So that the company can avoid financial distress that causes bankruptcy in the future.